Synthesis of the Butanamide Derivative S 19812, a New Dual Inhibitor of Cyclooxygenase and Lipoxygenase Pathways - Tordjman, Charles; Sauveur, Freédeéric; Droual, Monique; Briss, Sylvie; Andrea, Nathalie; Bellot, Isabelle; Deschamps, Christine; Wierzbicki, Michel (Arzneimittelforschung, 2003)
The general synthetic pathway and the interactions with arachidonic acid metabolism of the new compound S 19812 (N-hydroxy-N-methyl 4-(2,3-bis-(4-methoxyphenyl)-thiophen-5-yl)butanamide, CAS 181308-68-9) were investigated. S 19812 was selected for its well balanced dual inhibition of cyclooxygenase and 5-lipoxygenase pathways in vitro in rat polymorphonuclear neutrophils (PMNs) (IC50 PGE2: 0.10 µmol/l, LTB4: 0.07 µmol/l) and ex vivo in mice blood (ED50 PGE2: 13.1 mg/kg, LTB4: 20.8 mg/kg). These properties make this drug a promising therapeutic agent for pain and inflammation associated with osteoarthritis.
Keywords: Butanamide derivative; CAS 181308-68-9; Cyclooxygenase; Lipoxygenase; S 19812, inhibition of cyclooxygenase and lipoxygenase, in vitro and ex vivo studies, synthesis